Validation of an Extensive CYP2D6 Assay Panel Based on Invader and TaqMan Copy Number Assays. (15th October 2019) - Leung, Edward Ki Yun; Agolini, Emanuele; Pei, Xun; Melis, Roberta; McMillin, Gwendolyn A; Friedman, Paula N; Peterson, Patrick; Danahey, Keith; O'Donnell, Peter H; Yeo, Kiang-Teck J
Abstract: Background: CYP2D6 is involved in the oxidative metabolism of approximately 20% of all clinically used medications. Genotyping cytochrome P450, family 2, subfamily D, polypeptide 6 (CYP2D6), is a challenge because of the high complexity of the locus. Methods: Twenty-nine CYP2D6 sequence variants were genotyped in 50 deidentified patient samples and 29 Coriell DNAs by Invader assay, and results were compared with Infiniti assay and Sanger sequencing. To determine CYP2D6 copy number, 3 TaqMan real-time hydrolysis probes were used and results were compared with long-range PCR. Discrimination of the duplicated alleles was done on 17 DNA samples with 3 copies of CYP2D6 by long-range PCR followed by Invader genotyping and single nucleotide extension for the comparison. Results: Complete concordance was observed for all samples between platforms except for 2 samples due to the lack of the *45 allele in the Infiniti panel. Reproducibility with the Invader assay and TaqMan copy number was 100%. Analytical sensitivity using DNA with 2 copies was determined to be 10 ng DNA for the Invader assay and 1 ng/μL DNA for the TaqMan assay, respectively. Complete concordance and reproducibility were observed for duplicated allele discrimination with the exception of 1 sample, determined to be *29/*43X2 by the Invader test and *1X2/*29 by the Infiniti method, which did not test for *43. Conclusions: This validation study showed that Invader and TaqMan assay combined panel provides an attractive, valid, highly accurate, and reproducible approach for CYP2D6 genotyping for clinical implementation.